The Effectiveness of Functional Electrical Stimulation (FES) in On-Off Mode for Enhancing the Cycling Performance of Team Phoenix at 2016 Cybathlon - Kenry W.C. Leung; Raymond K.Y. Tong; Xiaojun Wang; Ginny T.Y. Lee; Peter M.K. Pang; H.W. Wai; H.C. Leung (PAGEPress Publications, 2017)
In this study we designed a Functional Electrical Stimulation (FES) trike for a female subject with spinal cord injury to exercise her lower limbs and improve her lower limb muscle condition for attending the 2016 Cybathlon FES bike competition. Our FES pilot was the only female participant, in the FES cycling competition and she rode for Team Phoenix from the Chinese University of Hong Kong. Due to the weakness of muscles in the lower limb of the subject, and due to scoliosis over her thoracolumbar aéra, the mechanical structure of the trike had to be tailor-made to ensure she sat on the bike in a safe and secure position. A six-phase angle-driven stimulation pattern was developed to stimulate quadriceps and hamstrings without gluteus muscles for contraction through four surface electrodes, thereby creating a cycling movement. To improve the cycling endurance and reduce the muscle fatigue, an on-off mode was developed for controlling the stimulation time that allowed the subject to cycle for 20s, then pause while the trike advanced without stimulation for 5s, followed by a subsequent 20 sec stimulation, to continue cycling. The pilot participated in the training procedure including training exercise at home, trike fitting in the trike by modifying the mechanical structure, and conducting the cycling exercise for six months. We observed significant improvements in the pilot's lower limb condition. The on-off mode enabled our pilot to extend her cycling endurance effectively, from 1 min to 2.5 mins and the distance from 62m to 100m. Over the eight minutes time limit, our team successfully finished 100 m in the Cybathlon FES.